Changes In Competitiveness Among The Visegrad Countries After Accession To The European Union: A Comparative Analysis Based On A Generalized Double Diamond Model; Zmiany konkurencyjnosći krajoẃ grupy wyszehradzkiej po akcesji do Unii Europejskiej: analiza poroẃnawcza. W oparciu o uogoĺniony model podwoj́nego diamentu przewag konkurencyjnych - Edward Molendowski; Małgorzata Zṁuda (Comparative Economic Research. Central and Eastern Europe, 2013)
National competitiveness is a buzzword that awakens much interest and controversy. In its broadest perspective, it is seen as a modern way of describing the development efforts of nations in the times of globalization (Reinert 2001, p. 23-42). This means that forces driving the changes in the global economy: liberalization of international trade, booming investment by multinational enterprises and development of regional integration groupings, need to be included into the competitiveness model. Well-known and commonly used approach to national competitiveness: Porter's diamond of competitive advantage does not however capture this international context. By concentrating solely on the elements of the domestic environment, the model does not show the complicated international linkages that have shaped the competitiveness of many countries. Especially in the case of small, open 'catching-up' economies, assessing national competitiveness solely on the basis of the potential of domestic companies, based on local conditions, does not fully reflect their developmental context, which is also driven by the complex networks of international interdependencies. Building upon the generalized double diamond model developed by Moon et al. (2000), this paper explores the extent to which economic relations with international partners and the activities of transnational corporations affect the competitiveness of the Visegrad Group countries, and how this relationship has been changing in the post-accession period. To answer the research problem posed, Eurostat and Global Competitiveness Report data have been gathered to assess the competitiveness variables on both the domestic/national and international levels. It has been shown that integration within the global economy constitutes an essential element of competitiveness for each of the analysed countries. – – Miedzynarodowa konkurencyjnosćǵospodarki narodowej to zagadnienie, ktoŕe wybudza wiele kontrowersji. W najszerszej perspektywie: to "wspoĺczesne" ujecie fundamentalnych problemoẃ rozwoju gospodarczego, osadzone w realiach globalizacji (Reinert, 2001, s. 23-42). Oznacza to, zė siły napedzajace rozwoj́ gospodarki globalnej: liberalizacja handlu miedzynarodowego, działalnosćínwestycyjna korporacji transnarodowych oraz zaciesńianie wspoĺpracy gospodarczej w ramach regionalnych ugrupowaníntegracyjnych, powinny zostacúwzglednione w modelu konkurencyjnosći. Jedno z najpopularniejszych wielowymiarowych ujec\': diament przewag konkurencyjnych Portera skupia sie na zŕod́łach konkurencyjnosći przedsiebiorstw w ramach poszczegoĺnych gałezi przemysłu. Poprzez podnoszenie stopnia zaawansowania technologicznego firm, poprawia sie produktywnosććzynnikoẃ wytwoŕczych, co w efekcie przyczynia sie do rozwoju gospodarczego i wzrostu standardu zẏcia ludnosći. Pomimo popularnosći tego ujecia, nie znajduje ono zastosowania dla wszystkich krajoẃ. Szczegoĺnie w przypadku małych, doganiajacych gospodarek otwartych, ktoŕych rozwoj́ jest w duzėj mierze uzalezṅiony od efektywnej integracji w ramach miedzynarodowego podziału pracy, spojrzenie na zŕod́ła konkurencyjnosći jedynie przez pryzmat warunkoẃ wewnetrznych jest niekompletne. Bazujac na uogoĺnionym modelu podwoj́nego diamentu przewag konkurencyjnych Moona (2000), w niniejszym artykule, podjeto prob́e odpowiedzi na pytanie: w jak duzẏm stopniu powiazania gospodarcze z partnerami miedzynarodowymi oraz działalnosćḱorporacji transnarodowych wpływały na kształtowanie przewagi konkurencyjnej firm z krajoẃ grupy Wyszehradzkiej oraz jak rola ta zmieniała sie w przypadku kazḋego z tych panśtw w okresie poakcesyjnym. W celu udzielenia odpowiedzi na to pytanie badawcze, zgromadzono dane z baz Eurostat oraz wskazńiki Global Competitiveness Report aby oszacowacźmienne na poziomie krajowym i miedzynarodowym. Wyniki przeprowadzonej analizy potwierdzaja, zė integracja w ramach gospodarki globalnej to wazṅy element konkurencyjnosći kazḋego z krajoẃ grupy Wyszehradzkiej.
Keywords: 330; international competitiveness; Visegrad Group countries; Porter's diamond; double diamond model; small open economy